Transformational Leadership Senior Assistant Co-curriculum: The Relationship between Perspectives and Satisfaction Among Secondary School Sports and Games Club Advisory Teachers - Nguang Ung Siong; Lau Siew Hung (Journal of Social Transformation and Regional Development, 2021)
This study was conducted to identify the relationship between the perspective and satisfaction of school sports and games club advisory teachers on the transformational leadership of Senior Assistant Co-curriculum in Secondary schools. This study is a comparative causal study and uses the Group Sampling method involving 550 secondary school teachers in Sarawak. Pearson correlation results r = .796, p